2021
DOI: 10.3390/toxins13070436
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combined Bee Venom Acupuncture and NSAID Treatment for Non-Specific Chronic Neck Pain: A Randomized, Assessor-Blinded, Pilot Clinical Trial

Abstract: This study aimed to investigate the feasibility of a combined treatment of bee venom acupuncture (BVA) and non-steroidal anti-inflammatory drugs (NSAIDs) for the treatment of non-specific chronic neck pain (NCNP). Patients with NCNP for ≥3 months were randomly allocated to a BVA, NSAIDs, or combined group (1:1:1), receiving 6 sessions of BVA, loxoprofen (180 mg daily), or a combination, respectively, for 3 weeks. Recruitment, adherence, and completion rates were calculated to assess feasibility. Bothersomeness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The high citation rate of SPINE indicates that CP related to spine is the focus of acupuncture for CP. 69,[73][74][75][76][77][78][79][80][81][82][83][84][85][86][87] From the perspective of research areas, electroacupuncture, low back pain, systematic review, randomized controlled trial, meta analysis are the main research focuses, which shows that researchers are very interested in verification of the effectiveness on acupuncture for CP. Trials to prove the effectiveness of acupuncture in the treatment of pain is and will be the focuses of this research field.…”
Section: Discussionmentioning
confidence: 99%
“…The high citation rate of SPINE indicates that CP related to spine is the focus of acupuncture for CP. 69,[73][74][75][76][77][78][79][80][81][82][83][84][85][86][87] From the perspective of research areas, electroacupuncture, low back pain, systematic review, randomized controlled trial, meta analysis are the main research focuses, which shows that researchers are very interested in verification of the effectiveness on acupuncture for CP. Trials to prove the effectiveness of acupuncture in the treatment of pain is and will be the focuses of this research field.…”
Section: Discussionmentioning
confidence: 99%
“…The South Korean researchers focused on Pharmacopuncture, , specifically bee venom acupuncture. Multiple RCT tests have demonstrated that bee venom acupuncture is effective in relieving pain and treating arthritis 30 . The USA researchers focused more on acupuncture's role in pain treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Occlusal appliances in conjunction with NSAIDs [ 29 ], mobilisation of the upper cervical region and craniocervical flexor training [ 30 ] were also effective for orofacial pain. In regard to pharmacopuncture, previous RCT revealed that bee venom pharmacopuncture for nonspecific chronic neck pain had a significantly better effect on the VAS scores for pain and bothersomeness than NSAIDs and combination therapy [ 31 ]. Another RCT reported that Angelica sinesis pharmacopuncture was significantly more effective for reducing the VAS score for pain [ 32 ].…”
Section: Discussionmentioning
confidence: 99%